Severe case of fetal hemolytic disease caused by anti‐Cw requiring serial intrauterine transfusions complicated by pancytopenia and cholestasis. Issue 1 (23rd October 2015) - Macher, Susanne; Wagner, Thomas; Rosskopf, Konrad; Reiterer, Friedrich; Csapo, Bence; Schlenke, Peter; Klaritsch, Philipp
Abstract : BACKGROUND: Anti‐C w are rarely found as a source for severe fetal and neonatal hemolytic diseases. We report a case with serial intrauterine transfusions complicated by pancytopenia and cholestasis in the neonatal period. CASE REPORT: A 37‐year‐old woman revealed anti‐C w with a titer of 512 in her fourth pregnancy. The fetus developed fetal anemia and a severe hydrops requiring three intrauterine red blood cell (RBC) transfusions. After birth at 33 + 0 weeks the newborn presented only transfused RBCs and suffered from anemia, thrombocytopenia, leukopenia, and a cholestatic liver disease. Blood counts improved after transfusion of 2 RBC units and one platelet concentrate and administration of hematopoietic growth factors. The symptoms of cholestasis improved slowly after therapy with ursodeoxycholic acid, vitamins, and medium‐chain triglyceride‐enriched formula feeding. CONCLUSION: Anti‐C w may lead to severe fetal anemia and consecutive complications. Surveillance of affected pregnancies with high antibody titers using sonographic evaluation of the middle cerebral artery peak systolic velocity should be warranted, especially in multiparous women.